AN AUDIT OF ACUTE LEUKAEMIA IN A NIGERIAN TERTIARY INSTITUTION - John Ayodele Olaniyi; Garba Kangiwa Umar (Mediterranean Journal of Hematology and Infectious Diseases)
Objective: The current burden of acute leukaemias in this centre remains obscure and hence this study was carried out to audit acute leukaemias seen between May 2003 and July 2008 to determine the burden and the frequency rates of acute leukaemia subtypes in this tertiary center Settings: Tertiary referral centre in the South Western part of Nigeria: The University College Hospital, Ibadan. Methods: This is a retrospective analysis of case notes, complimented by the Departmental records (the “pink cards”) of all acute leukaemias seen within the stipulated period. The diagnosis of each acute leukaemia was made predominantly through clinical features morphology by a team of Haematologists. Results: A total of 50 cases of acute leukaemia were diagnosed and treated within the period of study. There were 34 males and 16 females, ratio 2.1:1. Age range was 2-60 years. The mean age was 19yrs. Out of the 50 acute leukaemias, 28 cases (19 males and 9 females (M:F ratio of 2:1)) were diagnosed as AML with age range of 4-60 years(x=21.4yrs) while 22 cases were diagnosed as ALL, made up of 15 males and 7 females (M:F ratio of 2:1) and a mean age of 20.4yrs.. Conclusion: Acute leukaemias constitute a significant burden in our institution and the general outcome remains very poor being characterized by early death rate. Improving survival rate of acute leukaemias will require facility and manpower upgrading to improve diagnosis of distinct clinicopathologic entities, treatment modalitiest, subsidizing cancer care so that best drugs can be applied, and commencing as soon as possible the application of stem cell transplant amongst others.